Penyelesaian Sengketa Batas Wilayah Melalui Pengujian Undang-Undang di Mahkamah Konstitusi - Jayanti puspitaningrum (Jurnal Konstitusi, 2020)
This research discusses the interpretation of the Constitutional Court in reviewing laws regarding the formation of regions whose decisions grant the petitioner’s petition which have implications for changes in territorial boundaries, namely the Constitutional Court Decision No. 127 / PUU-VII / 2009. There are two problems examined in this research, namely (1) How is the interpretation of the Constitutional Court in resolving territorial boundary disputes through testing the laws in review of the 1945 Constitution; (2) How the design of territorial boundary dispute resolution constitutionally. The research method used is normative juridical research using a conceptual approach. In addition, it is reviewed with case studies related to the material being studied. The results of this study are (1) Based on the review of the Constitutional Court decision no. 127 / PUU-VII / 2009 which granted the request for judicial review of Law No. 56 of 2008 concerning the Establishment of Tambrauw Regency, the Constitutional Court stated that the legislators had ignored the aspirations of the people of Tambrauw Regency who had divided its territory from 10 (ten) districts into 5 (five) districts. This decision implied that 5 districts were re-entered into Law no. 56 of 2008 added 1 (one) district namely Fef District so that Tambrauw Regency has 11 (eleven) districts. Second, the design for the settlement of territorial boundaries is regulated in Permendagri Number 141 of 2017 and Law Number 23 of 2014, namely through Administrative (nonlegal) settlement by the Governor and the Minister of Home Affairs. In addition, legal dispute resolution is carried out through the Minister of Home Affairs’ judicial review rights at the Supreme Court and the Constitutional Court through judicial review of regional formation laws.